On the road [videorecording (DVD)] - Riley, Sam, 1980-; Hedlund, Garrett, 1985-; Stewart, Kristen, 1990-; Adams, Amy; Dunst, Kirsten, 1982-; Mortensen, Viggo, 1958-; Kerouac, Jack, 1922-1969 (Sundance Selects : MPI Media Group, 2013)
Traveling cross-country, young writer Sal Paradise has his life shaken by the arrival of free-spirited Dean Moriarty and his girl, Marylou. As they travel across the country, they encounter a mix of people who each impact their journey indelibly.